THE EFFECT OF PROFITABILITY, LEVERAGE, AND CAPITAL INTENSITY ON TAX AVOIDANCE WITH COMPANY SIZE AS A MODERATING VARIABLE IN MANUFACTURING COMPANIES LISTED ON THE IDX - Fadillah, Nur; Lestari, Dini Martinda; Afriani, Raden Irna (International Journal of Multidisciplinary Research and Literature, 2024)
Companies often use tax avoidance to take advantage of tax weaknesses. This study aims to examine the effect of profitability, leverage and capital intensity on tax avoidance and company size that moderates profitability, leverage and capital intensity on tax avoidance in manufacturing companies listed on the IDX in 2019-2023. The research method used is an associative method with a quantitative approach. The population in this study are manufacturing companies listed on the IDX in 2019-2023. The sampling technique uses purposive sampling so that the samples obtained are nine companies and 5 years of observation. The analysis used is the classical assumption test, Moderate Regression Analysis (MRA) and hypothesis testing. The results of this study state that the profitability variable (X1) obtained a calculated t value = -1.351 <t table 2.6216 with a significance level of 0.185 > 0.05, so H0 is accepted, and H1 is rejected, the leverage variable (X2) obtained a calculated t value = -3.879 <t table 2.6216 with a significance level of 0.000 <0.05, so H0 is rejected, and H2 is accepted, the capital insensitivity variable (X3) obtained a calculated t value = -4.848 <t table 2.6216 with a significance level of 0.000 <0.05, so H0 is rejected, and H3 is accepted, the capital insensitivity variable (X3) obtained a calculated t value = -4.848 <t table 2.6216 with a significance level of 0.000 <0.05, so H0 is rejected, and H3 is accepted. Accepted, the interaction between profitability and company size variables (X1*Z) obtained a t-value of 1.266 <t table 2.03452 with a significance level of 0.213> 0.05, then H0 is accepted, and H¬4 is rejected, the interaction between leverage and company size variables (X2*Z) obtained a t-value of -3.901 <t table 2.03452 with a significance level of 0.000> 0.05, then H0 is rejected, and H5 is accepted, the interaction between capital insensitivity and company size variables (X2*Z) obtained a t-value of -4798 <t table 2.03452 with a significance level of 0.000> 0.05, then H0 is rejected and H6 is accepted. The conclusion of this study shows that profitability does not partially affect tax avoidance, and leverage and capital intensity affect it. The company size does not moderate the effect of profitability on tax avoidance, while it moderates the effect of leverage and capital intensity on tax avoidance